Analysis of Factors that Influence the Implementation of Technological Innovation in the Indonesian Public Sector - Bilal Aslam; Usman Tariq; Omar Ahmad (Journal of Loomingulisus ja Innovatsioon, 2024)
The implementation of technological innovation in the public sector is a critical driver of efficiency, transparency, and service delivery in many countries, including Indonesia. Despite the increasing importance of technology in public administration, the adoption and effective implementation of technological innovations in the Indonesian public sector face various challenges, including organizational resistance, inadequate infrastructure, and limited digital skills. This study aims to analyze the factors that influence the successful implementation of technological innovations in Indonesian public institutions. Using a mixed-methods approach, the research integrates qualitative interviews with key public sector managers and quantitative surveys of public sector employees to identify the critical factors that facilitate or hinder the adoption of technology. The findings highlight that leadership commitment, organizational culture, availability of resources, and training programs are significant drivers of successful technological implementation. Conversely, barriers such as budget constraints, political factors, and a lack of technical expertise were found to limit the effectiveness of technological innovation. The study concludes that for successful technological innovation in the Indonesian public sector, it is crucial to focus on strengthening leadership, fostering a supportive organizational culture, and investing in infrastructure and training programs. These findings provide practical recommendations for policymakers and public sector managers in Indonesia.